2014
DOI: 10.1016/j.yjmcc.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

BDNF secretion by human pulmonary artery endothelial cells in response to hypoxia

Abstract: Within human pulmonary artery, neurotrophin growth factors [NTs; e.g. brain-derived neurotrophic factor (BDNF)] and their high-affinity receptors (tropomyosin-related kinase; Trk) and low-affinity receptors p75 neurotrophin receptor (p75NTR) have been reported, but their functional role is incompletely understood. We tested the hypothesis that BDNF is produced by human pulmonary artery endothelial cells (PAECs). In the context of hypoxia as a risk factor for pulmonary hypertension, we examined the effect of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 43 publications
3
72
1
1
Order By: Relevance
“…Although circulating BDNF may originate from the hippocampus, cerebral cortex, and basal forebrain, 58 it also may be derived from other cellular sources, including platelets, 59,60 smooth muscle cells, 35,61 and vascular endothelial cells. 62 This supports BDNF's role as a promoter of neuronal growth and survival both in the central and peripheral nervous system. However, it is unclear whether circulating BDNF values measured in this study are representative of central nervous system values.…”
Section: Diagnostic and Prognostic Value Of Bdnf In Tbimentioning
confidence: 56%
“…Although circulating BDNF may originate from the hippocampus, cerebral cortex, and basal forebrain, 58 it also may be derived from other cellular sources, including platelets, 59,60 smooth muscle cells, 35,61 and vascular endothelial cells. 62 This supports BDNF's role as a promoter of neuronal growth and survival both in the central and peripheral nervous system. However, it is unclear whether circulating BDNF values measured in this study are representative of central nervous system values.…”
Section: Diagnostic and Prognostic Value Of Bdnf In Tbimentioning
confidence: 56%
“…In terms of physiological and perceptual measures, a self-paced performance test will allow participants to regulate power output in such a way that the physiological and perceptual strain should be similar. For BDNF we expect an increase due to the combination of the higher ambient temperature and exercise (as was shown in the research of Goekint et al 2011), and even a possible further rise due to the addition of the altitude stressor (Helan et al 2014). The acute increase in BDNF is, however, expected to be small, and as such we further hypothesized that this would not be linked to an improved cognitive performance.…”
Section: Introductionmentioning
confidence: 82%
“…Two studies looked at the effects of chronic altitude exposure for at least 72 h (Li et al 2012;Helan et al 2014). Their outcomes are contradictory, Li et al (2012) showed a decrease in BDNF concentration after a 5-day acclimatization period at 3900 m, while Helan et al (2014) observed increased BDNF levels after 72 h at 3350 m. Both hypoxia and BDNF increased hypoxia-inducible factor 1 (Helan et al 2014), a factor that is considered as an important regulator in the hypoxic response of the BBB (Ogunshola and Al-Ahmad 2012). The discrepancy in these findings and the lack of effect on an acute exposure, as observed in the present study, elucidate the necessity for further research on the effects of altitude on BDNF, and the potential mechanisms involved.…”
Section: Cognitive Performance and Bdnfmentioning
confidence: 99%
See 2 more Smart Citations